2009
DOI: 10.1098/rspb.2008.1931
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transoceanic migrations by loggerhead sea turtles in the southern Pacific Ocean

Abstract: Post-hatchling loggerhead turtles (Caretta caretta) in the northern Pacific and northern Atlantic Oceans undertake transoceanic developmental migrations. Similar migratory behaviour is hypothesized in the South Pacific Ocean as post-hatchling loggerhead turtles are observed in Peruvian fisheries, yet no loggerhead rookeries occur along the coast of South America. This hypothesis was supported by analyses of the size-class distribution of 123 post-hatchling turtles in the South Pacific and genetic analysis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 25 publications
3
86
1
Order By: Relevance
“…Thus, dispersal of individuals carrying WP haplotypes could be facilitated towards eastern regions either via the South Equatorial current in combination with the Humboldt Current from the south, or the North Equatorial current in combination with El Niño from the north. Previous satellite telemetry studies (C. caretta, D. coriacea, Eretmochelys imbricata: Mast et al 2016) and tag recovery from hatchlings captured in longline fisheries (C. caretta; Boyle et al 2009) have identified the importance of these dynamic oceanic currents in sea turtle movements. Thus, these currents could not only explain the presence of trans-Pacific haplotypes in the EP, but could also be responsible for the genetic patterns of connectivity reported here between GPS and MNP at a much smaller geographic scale.…”
Section: Foraging Groundsmentioning
confidence: 99%
“…Thus, dispersal of individuals carrying WP haplotypes could be facilitated towards eastern regions either via the South Equatorial current in combination with the Humboldt Current from the south, or the North Equatorial current in combination with El Niño from the north. Previous satellite telemetry studies (C. caretta, D. coriacea, Eretmochelys imbricata: Mast et al 2016) and tag recovery from hatchlings captured in longline fisheries (C. caretta; Boyle et al 2009) have identified the importance of these dynamic oceanic currents in sea turtle movements. Thus, these currents could not only explain the presence of trans-Pacific haplotypes in the EP, but could also be responsible for the genetic patterns of connectivity reported here between GPS and MNP at a much smaller geographic scale.…”
Section: Foraging Groundsmentioning
confidence: 99%
“…This hypothesis is corroborated by multiple studies showing that the size and spatial distributions of oceanic juveniles captured at sea or found stranded display patterns that are consistent with transport by major currents downstream of the nesting beaches (Carr 1986b, Collard & Ogren 1990, Bolten et al 1993. Genetic analyses have also been able to track these juveniles back to their natal rookeries that, indeed, prove to be upstream of the place where they were found (Bowen et al 1995, 2007, Bolten et al 1998, Boyle et al 2009). More recently, studies combining genetic data with surface current analyses have indicated that current patterns also play an important role in determining the genetic structure of juvenile foraging aggregations (Carreras et al 2006, Bass et al 2006, Blumenthal et al 2009, Monzón Argüello et al 2010, Amorocho et al 2012, further reinforcing the idea that the juveniles' dispersal is largely driven by oceanic currents.…”
Section: Introductionmentioning
confidence: 99%
“…Parallels between ocean currents and MSA have been made for mixed stocks of green, loggerhead and hawksbill turtles in all oceans (e.g. Luke et al 2004, Bass et al 2006, Carreras et al 2006, Blumenthal et al 2009, Boyle et al 2009, Jensen 2010, Monzón-Argüello et al 2010; all these studies conclude that the compositions of mixed stocks depend on major and minor current systems. The description of sea turtle dispersal based on surface drifter tracks has long been proposed (e.g.…”
Section: Introductionmentioning
confidence: 99%